POLA ASUH ORANG TUA DALAM MEMBENTUK KARAKTER ANAK SELAMA PANDEMI DI LINGKUNGAN III KECAMATAN MEDAN AEA KELURAHAN PASAR MERAH TIMUR - Devi Kartika Ayu (Fakultas Agama Islam, 2021)
Parenting patterns of parents in shaping the character of children during the pandemic there are differences in the way of parenting. There are parents who give freedom, there are those who expect their children to obey the rules without question. There are parents who give a lot of input and direction on what their children do, and there is little room for reciprocal dialogue between parents and children. The formulations of this research are: 1) How is parenting style in shaping the character of children during the pandemic in environment II Pasar Merah Timur sub-district 2) What factors influence parents in shaping children's character during the pandemic in environment II Pasar Merah Timur sub-district 3 ) What is the strategy of parents in shaping the character of their children during the pandemic in the second neighborhood of the Pasar Merah Timur sub-district. The type of research is qualitative research or field research. Collecting data using observation, interview, and documentation techniques. This study concludes that: 1) Parenting patterns in shaping the character of children there are differences in the way parents care for their children, there are parents who give freedom and guidance to children. Parents give a lot of input and direction on what their children do, there are parents who have little room for reciprocal dialogue between parents and children, expect children to obey the rules without question and also parents who provide little emotional support to children. 2) The factors that influence parents in implementing parenting patterns for their children are the level of education of the parents, the economic status and occupation of the parents, and the personality of the parents. 3) The strategy of parents in shaping the child's character includes exemplary, habituation and creating conducive conditions.